Atherosclerosis, Dyslipidemia, and Inflammation: The Significant Role of Polyunsaturated Fatty Acids - Dessì, Mariarita (Hindawi Publishing Corporation, 2013)
Phospholipids play an essential role in cell membrane structure and function. The length and number of double bonds of fatty acids in membrane phospholipids are main determinants of fluidity, transport systems, activity of membrane-bound enzymes, and susceptibility to lipid peroxidation. The fatty acid profile of serum lipids, especially the phospholipids, reflects the fatty acid composition of cell membranes. Moreover, long-chain n-3 polyunsatured fatty acids decrease very-low-density lipoprotein assembly and secretion reducing triacylglycerol production. N-6 and n-3 polyunsatured fatty acids are the precursors of signalling molecules, termed “eicosanoids,” which play an important role in the regulation of inflammation. Eicosanoids derived from n-6 polyunsatured fatty acids have proinflammatory actions, while eicosanoids derived from n-3 polyunsatured fatty acids have anti-inflammatory ones. Previous studies showed that inflammation contributes to both the onset and progression of atherosclerosis: actually, atherosclerosis is predominantly a chronic low-grade inflammatory disease of the vessel wall. Several studies suggested the relationship between long-chain n-3 polyunsaturated fatty acids and inflammation, showing that fatty acids may decrease endothelial activation and affect eicosanoid metabolism.